THE EFFECTS OF URBAN EXPANSION ON LIVELIHOOD ASSETS IN OYI LOCAL GOVERNMENT AREA OF ANAMBRA STATE - Ikeanyionwu, Uchechukwu Jacinta; Okoye, Chinedu Oguejiofo; Ukah, Chinomso (SciencePlus, 2025)
Rapid urbanization in Oyi LGA, driven by population growth due to proximity to Onitsha and the emergence of major markets, is causing significant socioeconomic and environmental challenges and has driven the purpose of this work. This study assessed the effects of urban expansion on people’s livelihood assets in the Oyi Local Government Area of Anambra State. The study's objectives were to assess how urban expansion has affected the different capitals of livelihood. The study employed a survey design and primary data was collected using a structured questionnaire. A total of 391 households were used for the study. Findings indicate that urban expansion has positively influenced human, financial, and physical capital, and significant negative impacts were observed on natural capital and social capital. The research highlights the need for balanced urban development strategies that enhance economic opportunities while mitigating environmental degradation and preserving social fabric. Hence the study recommended that the relevant authorities enforce environmental impact assessments, invest in community-based initiatives to strengthen social cohesion, and establish transparent, participatory urban planning processes.